Analysis of the Financial Performance of Manufacturing Companies Before and During the Covid 19 Pandemic - Mazliza Mazliza; Arum Kusumaningdyah Adiati (International Journal Labs, 2023)
Corona virus or commonly known as Covid 19 is a virus that can cause disturbances in the respiratory system to problems in the lungs. The first case of the virus occurred in December 2019 in the Chinese city of Wuhan. This study aims to determine the financial performance condition of manufacturing companies listed on the Indonesia Stock Exchange before and during the Covid-19 pandemic. The sample in this study amounted to 426 observations from 142 manufacturing sector companies listed on the Indonesia Stock Exchange in 2019 – 2021. The manufacturing company was chosen as the object of research because this company is engaged in the real sector which has various types of businesses and the number of companies dominates more than other companies so that it is felt that manufacturing companies can provide a big picture of the impact of the covid 19 pandemic. The test used in this study used the Wilcoxon ranked signed rank test method. The results showed that there was a difference between the profitability variable and the activity variable which was measured using return on assets and total assets turnover before the pandemic and during the Covid-19 pandemic. Meanwhile, the liquidity and solvency variables measured using the current ratio and debt to equity ratio have no difference between before the Covid-19 pandemic and during the Covid-19 pandemic.